Islam and law in Lebanon Sharia within and without the state - Clarke, Morgan 1972- (Cambridge University Press, 2018)
The modern state of Lebanon, created after the fall of the Ottoman Empire, is home to eighteen officially recognised different religious communities (or sects). Crucially, political office and representation came to be formally shared along confessional lines, and the privileges of power are distributed accordingly. One such key prerogative is exclusivity when it comes to personal status laws: the family legal affairs of each community. In this book, Morgan Clarke offers an authoritative and dynamic account of how the sharia is invoked both with Lebanon's state legal system, as Muslim family law, and outside it, as a framework for an Islamic life and society. By bringing together an in-depth analysis of Lebanon's state-sponsored sharia courts with a look at the wider world of religious instruction, this book highlights the breadth of the sharia and the complexity of the contexts within which it is embedded